Are obese rats influenced by GLP1 and IR through aerobic exercise? A case study - Ali Sayyah; Hamid Mohebbı; Hamid Arazı; Abbas Baharı (Türk Spor ve Egzersiz Dergisi)
The present study aimed to consider the influence of aerobic exercise intensity on GLP-1and IR in obese rats. Glucagon-like peptide-1 (GLP-1) is characterized as incretion hormones secreted from the intestine upon ingestion of food to maximize insulin secretion, regulate blood sugar and enhance insulin resistance (IR). It was an in vitro study. The study subjects were thirty-two male Wistar rats which were divided into 4 groups: three levels of aerobic training intensity (high, moderate and low intensity) and one control group. Following 8 weeks of different intensity of aerobic trainings, the researchers calculated plasma concentration of glucose, insulin, HOMA-IR and GLP-1. We applied dependent t-test and Analysis of variance (ANOVA) to test the research hypotheses. Body weight, BMI, insulin, blood glucose and HOMA-IR in high, moderate and low intensity of aerobic training were noticed to be significantly lower than in the control group (P=0.001) following an eight-week intervention. However, moderate and high intensity of aerobic training compared with low intensity significantly showed a decrease in insulin, blood glucose, HOMA-IR, and GLP-1. The findings revealed that moderate and high intensity of aerobic training results in GLP-1 secretion impairment, thus its improvement can cause a reduction in insulin resistance and blood glucose regulation.